7 - Book Reviews: A Modern Economic History of Africa. Vol. 1 - The Nineteenth Century, by Paul Tiyambe Zeleza, publisher: CODESRIA, Dakar; distributor: ABC, Oxford, 1993, 501 p., 51. bibl., 23 p. index, 5 maps.: by Mohamed Mbodj - Mohamed Mbodj (Africa Development, 1993)
Abstract